Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2019
DOI: 10.1016/j.envint.2019.03.069
|View full text |Cite
|
Sign up to set email alerts
|

A comparative assessment of dilution correction methods for spot urinary analyte concentrations in a UK population exposed to arsenic in drinking water

Abstract: Spot urinary concentrations of environmental exposure biomarkers require correction for dilution. There is no consensus on the most appropriate method, with creatinine used by default despite lacking theoretical robustness. We comparatively assessed the efficacy of creatinine; specific gravity (SG); osmolality and modifications of all three for dilution correcting urinary arsenic. For 202 participants with urinary arsenic, creatinine, osmolality and SG measurements paired to drinking water As, we compared the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
100
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 37 publications
(106 citation statements)
references
References 31 publications
(49 reference statements)
5
100
0
1
Order By: Relevance
“…In our case-cohort studies, we did not observe strong differences in hazard ratio estimates after adjustment for creatine versus osmolality [19,20]. Two other studies showed osmolality adjustment to be superior to creatinine adjustment in associations with predictors of exposure or urinary flow rate [17,18], in line with the presupposition that osmolality may be less susceptible to underlying physiology or pathophysiology, such as differences in muscle catabolism, in comparison with creatinine. Nonetheless, both measures appear to be influenced by BMI, sex, and other covariates (results not shown), suggesting that covariate-adjusted standardization, which has been proposed for creatinine [21], may also be useful when correcting urinary biomarker concentrations for osmolality.…”
Section: Discussionsupporting
confidence: 74%
See 1 more Smart Citation
“…In our case-cohort studies, we did not observe strong differences in hazard ratio estimates after adjustment for creatine versus osmolality [19,20]. Two other studies showed osmolality adjustment to be superior to creatinine adjustment in associations with predictors of exposure or urinary flow rate [17,18], in line with the presupposition that osmolality may be less susceptible to underlying physiology or pathophysiology, such as differences in muscle catabolism, in comparison with creatinine. Nonetheless, both measures appear to be influenced by BMI, sex, and other covariates (results not shown), suggesting that covariate-adjusted standardization, which has been proposed for creatinine [21], may also be useful when correcting urinary biomarker concentrations for osmolality.…”
Section: Discussionsupporting
confidence: 74%
“…A few recent studies compared the impact of different methods of dilution adjustment on exposure estimates or disease outcomes [16][17][18][19][20]. One study showed no difference in associations between creatinine adjustment and osmolality adjustment using metabolomic data in a small study of 51 samples [16].…”
Section: Discussionmentioning
confidence: 99%
“…In the context of this study, corrections with creatinine may be questionable due to the prevalence of malnutrition, with low protein intake within the Pakistani population (Aziz & Hosain, 2014;GoP/UNICEF, 2018). By contrast, correction with specific gravity may be a more reliable approach as it is also considered a proxy for osmolality-the most reliable approach for urinary dilution correction (Middleton et al, 2018(Middleton et al, , 2019Watts et al, 2019). However, there are limited data available on, or discussion about, utilising alternative correction methods to creatinine.…”
Section: Discussionmentioning
confidence: 99%
“…However, our study has its limitations. The concentration of compounds in the urine may be affected by urine volume; the specific gravity (SG) of urine samples has been employed to reduce the urinary dilution effect [ 39 ]. Meanwhile, some individual EDCs interacting with the endocrine system were not included in this study, such as polybrominated diphenyl ethers (PBDE) [ 40 ], polychlorinated biphenyls [ 41 ], and perfluorooctane sulfonate (PFOS) [ 42 ].…”
Section: Discussionmentioning
confidence: 99%